Design Operability and Retrofit Analysis (DORA) framework for energy systems - Andiappan, Viknesh (Animo Repository, 2017)
© 2017 Elsevier Ltd A systematic framework for Design Operability and Retrofit Analysis (DORA) is presented. DORA is a framework explicitly analyzing energy system design containing process units functioning at different levels of operability. To express the operability of individual process units, DORA uses inoperability input-output modeling (IIM) approach. Based on IIM, a simple mixed integer linear programming (MILP) model is developed to analyze the impact of individual process unit inoperability on the flexibility of an energy system design. In the case where a design is deemed to possess insufficient flexibility to meet demands, DORA framework subsequently entails a step-by-step guide to debottleneck and retrofit a given design based on benefit-cost ratio (BCR). In this work, the DORA framework is demonstrated using a biomass-based tri-generation system (BTS) case study. As shown in the case study, DORA framework is used to determine whether a BTS facing a drop in individual unit efficiency, would require debottlenecking and retrofitting to increase its energy production.